Cutaneous leishmaniasis: a case report - BMM Kayastha; P Shrestha; R Shrestha; R Jahan (Nepal Journal of Dermatology, Venereology & Leprology)
Cutaneous Leishmaniasis (CL) is a vector-borne protozoal infection of the skin. It is endemic in the tropics and neotropics. Several species of Leishmania cause this disease in the Old World. It is manifested as chronic nodular to ulcerative lesions of the skin, which last for many months and may be disfiguring. Despite its increasing worldwide incidence, it is infrequently reported from Nepal. We are reporting a case of CL in a man who acquired the disease while working in Saudi Arabia and who was successfully treated with Sodium Stibogluconate injections.